Obesity Indicators and Health-related Quality of Life – Insights from a Cohort of Morbidly Obese, Middle-aged South Indian Women. Issue 2 (2020) - Ramasamy, Shobana; Joseph, Mini; Jiwanmall, Stephen Amarjeet; Kattula, Dheeraj; Nandyal, Munaf Babajan; Abraham, Vijay; Samarasam, Inian; Paravathareddy, Sandhiya; Paul, Thomas V; Rajaratnam, Simon; Thomas, Nihal; Kapoor, Nitin
No abstract available